Literature Review: Development Of Maritime Systems In The Digital Era - Riyadh, Muhammad; Syaifullah, Muhammad (Maritime Park: Journal of Maritime Technology and Society, 2025)
This systematic literature review examines the development of maritime systems in the digital era, focusing on technological advances, implementation challenges, and their impact on operational efficiency and environmental sustainability. The study analyzes recent developments in maritime digitalization, including Internet of Things (IoT) implementation, autonomous vessel technology, blockchain integration, and smart port systems. Through a comprehensive analysis of peer-reviewed publications from 2018 to 2024, the review reveals significant improvements in operational efficiency, with smart ports showing up to 35% increase in operational effectiveness and digital route optimization leading to 18% reduction in CO2 emissions. However, the research also identifies critical challenges, including a 300% increase in cyber attacks since 2020 and significant digital disparities between developed and developing regions, with adoption rates varying from 22% in Africa to 72% in North America. The findings indicate that while digital transformation in the maritime sector shows promising results in enhancing operational efficiency and environmental sustainability, issues of cybersecurity, standardization, and digital divide require urgent attention. The study projects substantial growth in maritime technology adoption, with 5G implementation expected to reach 60% by 2025 and autonomous operations projected to achieve 70% penetration by 2030.